Trends on the relationship between board size and financial and reputational corporate performance: The Colombian case - Luis Antonio Orozco; Jose Vargas; Raquel Galindo-Dorado (European Journal of Management and Business Economics (EJM&BE), 2018)
Purpose: The purpose of this paper is to investigate the relationship between board size (B-SIZE) and financial and reputational corporate performance in top companies ranked by the Business Monitor of Corporate Reputation- MERCO in Colombia. Design/methodology/approach: This paper conducts correlations and cluster analysis in order to classify firms based on performance and control variables, using a sectional sample of 84 large companies in Colombia over the period 2008-2012. Findings: This research founds that large boards are associated with high performance on corporate reputation, as stated by the resource dependence theory, and a low-financial performance, as predicted by the agency theory. However, the results indicate that there is no relation between financial and reputational performance. Research limitations/implications: This research considered only large companies listed by MERCO. Therefore, the results can only be generalized for top firms in Colombia according to this list. However, results add empirical evidence to theoretical debate between B-SIZE and firm performance considering financial and reputational indicators. Practical implications: According to the OECD manual of good corporate governance practices, the optimal B-SIZE has between five to nine core members. The board structure has a direct impact over the firm's financial and reputational performance and must be carefully analyzed by shareholders to balance the size according to expected results and firm's features like family ownership, exportation activities and norms of stock markets. Originality/value: This paper contributes to the existing literature on the relationship between B-SIZE and corporate performance with the evaluation of financial and reputational results for the case of an emerging economy. In Latin America, this analysis must go beyond OECD recommendations, and shall consider the context of an emerging country based on empirical evidence.
Keywords: 650; Corporate reputation; Organizational theory; Colombia; Financial performance; Board size